To multiply the polynomials \( (2x - 7)(3x^2 + 7x - 8) \), we will use the distributive property (also known as the FOIL method for binomials).
-
Multiply \( 2x \) by each term in the second polynomial:
- \( 2x \cdot 3x^2 = 6x^3 \)
- \( 2x \cdot 7x = 14x^2 \)
- \( 2x \cdot (-8) = -16x \)
-
Multiply \(-7\) by each term in the second polynomial:
- \(-7 \cdot 3x^2 = -21x^2\)
- \(-7 \cdot 7x = -49x\)
- \(-7 \cdot (-8) = 56\)
-
Now, combine all these results:
- \( 6x^3 + 14x^2 - 16x - 21x^2 - 49x + 56 \)
-
Combine like terms:
- For \(x^2\): \(14x^2 - 21x^2 = -7x^2\)
- For \(x\): \(-16x - 49x = -65x\)
So the resulting polynomial is: \[ 6x^3 - 7x^2 - 65x + 56 \]
Now, to fill in the coefficient responses:
- The value of the coefficient of the \(x^3\) term is 6.
- The value of the coefficient of the \(x^2\) term is -7.
- The value of the coefficient of the \(x\) term is -65.
- The value of the coefficient of the constant is 56.
So the final answers are:
- Coefficient of \(x^3\): 6
- Coefficient of \(x^2\): -7
- Coefficient of \(x\): -65
- Coefficient of constant: 56